2021
DOI: 10.3389/fcvm.2021.707508
|View full text |Cite|
|
Sign up to set email alerts
|

Diagnostic Accuracy and Generalizability of a Deep Learning-Based Fully Automated Algorithm for Coronary Artery Stenosis Detection on CCTA: A Multi-Centre Registry Study

Abstract: Aims: In this retrospective, multi-center study, we aimed to estimate the diagnostic accuracy and generalizability of an established deep learning (DL)-based fully automated algorithm in detecting coronary stenosis on coronary computed tomography angiography (CCTA).Methods and results: A total of 527 patients (33.0% female, mean age: 62.2 ± 10.2 years) with suspected coronary artery disease (CAD) who underwent CCTA and invasive coronary angiography (ICA) were enrolled from 27 hospitals from January 2016 to Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have assessed several AI applications for coronary artery assessment. In a retrospective multicenter study including 527 patients, a fully automated AI algorithm was not inferior to experts in the detection of coronary stenosis ≥50% and reduced the post-processing time significantly [17]. An accuracy of 84% and 86% for detecting ≥50% and ≥70% stenoses, respectively, was found in a CREDENCE substudy comparing AI quantitative coronary CTA with core lab quantitative coronary angiography [18].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies have assessed several AI applications for coronary artery assessment. In a retrospective multicenter study including 527 patients, a fully automated AI algorithm was not inferior to experts in the detection of coronary stenosis ≥50% and reduced the post-processing time significantly [17]. An accuracy of 84% and 86% for detecting ≥50% and ≥70% stenoses, respectively, was found in a CREDENCE substudy comparing AI quantitative coronary CTA with core lab quantitative coronary angiography [18].…”
Section: Discussionmentioning
confidence: 93%
“…Recently, the first reports have been published on the AI-based automated detection of coronary stenoses in CCTA ( 31 – 33 ). In a 2021 retrospective, multi-center study, the diagnostic accuracy and generalizability of an established DL-based fully automated algorithm in detecting coronary stenosis on CCTA has been shown to perform non-inferior to expert readers in detecting coronary stenoses ≥50% ( 34 ). In the vessel-based evaluation, the DL algorithm had a higher sensitivity (65.7%) and negative predictive value (NPV) (78.8%) than human expert readers.…”
Section: Clinical Applications Of Machine Learning Artificial Intelli...mentioning
confidence: 99%
“…A prospective study of patients with chest pain undergoing CCTA found that structured reporting platforms with the automated calculation of the Coronary Artery Disease Reporting and Data System (CAD-RADS) scores outperform manual classification by preventing human errors, improving data quality, and supporting the standardization of clinical decision-making [199]. For CCTA, a retrospective study found that a deep learningbased algorithm helped streamline CCTA reconstruction and interpretation workflows for CAD patients, significantly improving time efficiency and diagnostic consistency [200]. Deep learning algorithms for the automated interpretation of echocardiographic images offer the opportunity to remove the burden for highly trained individuals to conduct manual image analysis [201] and may eliminate some of the intensive training and skill maintenance required of operators [202] and reduce human error [203].…”
Section: Evolving Solutionsmentioning
confidence: 99%